Avian surfactant protein (SP)-A2 first arose in an early tetrapod before the divergence of amphibians and gradually lost the collagen domain. (February 2023) - Kunchala, Srinivasa Reddy; van Dijk, Albert; Veldhuizen, Edwin J.A.; Donnellan, Stephen C.; Haagsman, Henk P.; Orgeig, Sandra
Abstract: The air-liquid interface of the mammalian lung is lined with pulmonary surfactants, a mixture of specific proteins and lipids that serve a dual purpose-enabling air-breathing and protection against pathogens. In mammals, surfactant proteins A (SP-A) and D (SP -D) are involved in innate defence of the lung. Birds seem to lack the SP-D gene, but possess SP-A2, an additional SP-A-like gene. Here we investigated the evolution of the SP-A and SP-D genes using computational gene prediction, homology, simulation modelling and phylogeny with published avian and other vertebrate genomes. PCR was used to confirm the identity and expression of SP-A analogues in various tissue homogenates of zebra finch and turkey. In silico analysis confirmed the absence of SP-D-like genes in all 47 published avian genomes. Zebra finch and turkey SP-A1 and SP-A2 sequences, confirmed by PCR of lung homogenates, were compared with sequenced and in silico predicted vertebrate homologs to construct a phylogenetic tree. The collagen domain of avian SP-A1, especially that of zebra finch, was dramatically shorter than that of mammalian SP-A. Amphibian and reptilian genomes also contain avian-like SP-A2 protein sequences with a collagen domain. NCBI Gnomon-predicted avian and alligator SP-A2 proteins all lacked the collagen domain completely. Both avian SP-A1 and SP-A2 sequences form separate clades, which are most closely related to their closest relatives, the alligators. The C-terminal carbohydrate recognition domain (CRD) of zebra finch SP-A1 was structurally almost identical to that of rat SP-A. In fact, the CRD of SP-A is highly conserved among all the vertebrates. Birds retained a truncated version of mammalian type SP-A1 as well as a non-collagenous C-type lectin, designated SP-A2, while losing the large collagenous SP-D lectin, reflecting their evolutionary trajectory towards a unidirectional respiratory system. In the context of zoonotic infections, how these evolutionary changes affect avian pulmonary surface protection is not clear. Highlights: The vast majority of avian genomes contain an SP-A1 and an SP-A2 gene. All investigated avian genomes lack SP-D. Birds and mammals adopted two different strategies of adaptive simplification. The collagen domain of avian SP-A is considerably shorter than mammalian homologs.